Peran Guru Kristen Sebagai Imam dalam Memfasilitasi Transformasi Kehidupan Murid - Siahaan, Julieta Putri; Wardhani, M. Kusuma (Sekolah Tinggi Teologi IKAT Jakarta, 2023)
Christian education has a mission to guide students to achieve life transformation. In the educational process, philosophy influences the way teachers teach to the success of life transformation mission. Therefore, the role of Christian teacher must be present in facilitating a transforming educational process. As priest, teacher view students as the image of God. The purpose of this study is to determine the role of Christian teacher as priest in facilitating the transformation of students' lives. The author uses a research method in the form of a literature review. Teachers as a priest must first ensure that Christ is an example in their life so that teacher can radiate the love of Christ that touches the hearts of students through the role of the Holy Spirit who instills the truth and transforms the lives of students through the knowledge of the true God. Christian teacher as priest must pray for students, prevent bad situations from happening, become agents of recovery, build a mutually supportive classroom atmosphere, demand reasonable student learning outcomes, and facilitate student devotional activities. Teachers should equip themselves to God's truth and correct themselves for the application of truth in personal life and to subsequent writers to examine the challenges and solutions faced by teachers as priests. AbstrakPendidikan Kristen memiliki misi untuk membimbing murid mencapai transformasi kehidupan. Pada proses pendidikan, filsafat memengaruhi cara mengajar guru terhadap keberhasilan misi transformasi kehidupan tersebut. Oleh karena itu, peran guru Kristen harus hadir dalam memfasilitasi proses pendidikan yang mentransformasi. Sebagai imam, guru memandang murid sebagai gambar dan rupa Allah. Adapun tujuan dari penelitian ini untuk mengetahui peran guru Kristen sebagai imam dalam memfasilitasi transformasi kehidupan murid. Penulis menggunakan metode penelitian berupa kajian literatur. Guru sebagai imam harus memastikan dahulu bahwa Kristus menjadi teladan hidupnya sehingga dapat memancarkan kasih Kristus yang menyentuh hati murid lewat peran Roh Kudus yang menanamkan kebenaran serta mentransformasi kehidupan murid melalui pengenalan Allah yang sejati. Guru Kristen sebagai imam harus mendoakan murid, mencegah terjadinya situasi buruk, menjadi agen pemulihan, membangun suasana kelas yang saling mendukung, menuntut hasil belajar murid secara wajar, serta memfasilitasi kegiatan devosi murid. Saran bagi guru adalah memperlengkapi diri pada kebenaran Allah dan mengoreksi diri akan pengaplikasian kebenaran dalam kehidupan pribadi serta kepada penulis selanjutnya untuk mengkaji tantangan dan solusi yang dihadapi guru sebagai imam.